PENGARUH KOMPETENSI PEGAWAI TERHADAP KUALITAS PELAYANAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PONTIANAK - Nurul Masriyah Aziizir E.42008008 (FISIP Universitas Tanjungpura Pontianak, 2012)
The title of this research is “The Effect of Employee’s Competency to Service Quality in Population and Civil Registry Office in Pontianak Regency”. This research is supposed to know whether employee’s competency gives effect to service quality of Population and Civil Registry Office in Pontianak Regency or not. The title of this research was brought up based on the problem from society that consider the service cost is not suitable with the regulations and lack of human resources as operators. Therefore, the service takes long time. This research is kind of quantitative using simple linear regression statistic run test. According to the result, it found regression equation like this: Y= 1,704 + 1,04 X. Based on statistic data analysis, indicators are valid and the variables are reliable. Hypothesis result shows that rcount is bigger than rtable (0,6934 > 0,191) with significance level 1,986 so the receivable hypothesis in this research is there is positive and significant effect between employee’s competency and service quality.Keywords: employee’s competency and service quality.